Nutritional Status and Food Habits of Child Labor in Rangpur City, Bangladesh - Md Rafiul Islam; Jannatul Ferdous Promity; Khanam Maraj Afroz; Sadia Marjan Kaniz; Md. Razibul Hassan; Khandaker Fadwana Islam (Health Dynamics, 2024)
Background: In Bangladesh, the harsh reality of child labor persists, with over 8 million children engaged in such work. This not only deprives them of their childhood but also has severe implications for their mental and physical health. This study seeks to investigate the daily food intake and nutritional status of child laborers in Rangpur City, shedding light on the broader health impacts of child labor in this region. Methods: The study employed a structured questionnaire and anthropometric measurements to assess the socioeconomic status and dietary habits of participants. Pretesting ensured questionnaire accuracy, while daily and weekly recall methods captured comprehensive food consumption data. Socioeconomic inquiries included income, education, employment, and family details, providing a holistic understanding of participants' circumstances. Results: The survey highlights that most working children are aged 12-14, predominantly employed in mechanics and sales, working long hours under precarious conditions for low wages, primarily to support their families. Despite some attending primary school and receiving employer-provided meals and medical aid, these children struggle with inadequate education and nutrition, and a high incidence of workplace accidents. Conclusion: Child laborers have often poorer nutritional status than the average person. They are not provided with a proper diet. Consequently, they are dealing with various health problems.